Microstructural Evolution, Room‐ and High‐Temperature Mechanical Properties of Friction Welded Joints of a New Wrought Ni–Fe Based Superalloy. Issue 8 (11th June 2019) - Xu, Yaxin; Li, Wenya; Lu, Jintao; Wang, Guilong; Dang, Yingying; Yang, Zheng; Gu, Yuefeng; Yang, Zhiyuan; Sui, Yupeng
Abstract : A new wrought Ni–Fe‐based superalloy, designed for the advanced ultra‐supercritical power plant (A‐USC), is successfully joined by rotary friction welding (RFW), followed by post‐weld heat treatment (PWTH). The microstructural evolution and mechanical properties of the joints are systematically investigated by optical microscopy, scanning electron microscopy, microhardness, and tensile tests at both room temperature and 750 °C. The results show that dynamic recrystallization and dissolution of strengthening phases have occurred in the weld during FW, in which γ′ dissolves to a larger extent than M23 C6 or MC carbides. The microstructure of the as‐welded joint including the grain size, shape, and the distribution of precipitates gradually changes from the weldline to the parent alloy. Consequently, the as‐welded joints exhibit relatively poor mechanical properties due to the dissolution of γ′ which becomes even worse at 750 °C because of the grain‐boundary sliding. After PWHT, the as‐welded microstructure can be homogenized by grain growth and the re‐precipitation of strengthening phases, which is responsible for the remarkable improvement in tensile strength at both room and high temperature after PWHT. This study gives new insights into the high‐quality welding of the newly developed Ni–Fe‐based superalloy. Abstract : A new wrought Ni–Fe‐based superalloy is successfully joined by rotary friction welding. The relationship between the microstructural evolution and tensile properties of the weld as well as the effect of post‐weld heat treatment is investigated. Post‐weld heat treatment exerts a large impact on the weld microstructure and thus significantly improves the tensile strength at both room temperature and 750 °C.